Electrocardiographic differentiation between 'benign T-wave inversion' and arrhythmogenic right ventricular cardiomyopathy. Issue 2 (29th August 2018) - Finocchiaro, Gherardo; Papadakis, Michael; Dhutia, Harshil; Zaidi, Abbas; Malhotra, Aneil; Fabi, Elena; Cappelletto, Chiara; Brook, Joe; Papatheodorou, Efstathios; Ensam, Bode; Miles, Christopher J; Bastiaenen, Rachel; et al.
Abstract: Aims: To characterize the most common electrocardiographic (ECG) abnormalities in patients with arrhythmogenic right ventricular cardiomyopathy (ARVC), including anterior T-wave inversion (TWI) and to compare the characteristics of TWI in patients with ARVC and in a cohort of young healthy athletes and sedentary individuals. Methods and results: The study population consisted of 162 patients with a definite diagnosis of ARVC and 129 young controls with anterior TWI. Cardiac disease was excluded in all controls after a comprehensive diagnostic work-up. The ECG was abnormal in 131 patients with ARVC (81%). Abnormalities included anterior TWI ( n  = 82, 51%), QRS duration ratio V2:V5 >1.2 ( n  = 51, 31%), prolonged terminal S wave activation duration in V2 >55 ms ( n  = 42, 26%), inferior TWI ( n  = 30, 18%), and lateral TWI ( n  = 26, 16%). The J-point preceding anterior TWI was <0.1 mV in 80/82 (98%) patients with ARVC and in 98 (76%) controls. Among the ARVC patients with anterior TWI, 62 (77%) showed at least one additional abnormal feature, most commonly QRS duration ratio V2:V5 > 1.2 (52%) and inferior or lateral TWI (47%). Conclusion: The ECG is frequently abnormal in patients with ARVC and anterior TWI is the most common feature. Anterior TWI is usually accompanied by other abnormalities in ARVC, which are uncommon in healthy individuals. J point <0.1 mV preceding anterior TWI is not specific to ARVC and is observed in the majority of healthy individuals, including athletes, indicating a limited role for differentiating physiology or normal variants from ARVC.